Rocky Carzo with Bob Bass and Rich Giachetti (Tufts Archival Research Center, 2005)
Light on the Hill, the second volume of the history of Tufts University, was published in 1986, covering the years from 1952 to 1986. This doucument was created from the 1986 edition of Light on the Hill, Volume II.